2007
DOI: 10.1653/0015-4040(2007)90[33:impoms]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mating Performance of Mass-Reared Sterile Mediterranean Fruit Flies (Diptera: Tephritidae) Through Changes in Adult Holding Conditions: Demography and Mating Competitiveness

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Similar results were observed by Liedo et al (2007) and Díaz-Fleischer et al (2009), who evaluated cage density under laboratory conditions and found that low densities resulted in individuals with increased mating competitiveness. In the same sense, the highest fl ight ability for A. ludens was obtained in MX screen towers, as they have a larger ventilation area.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were observed by Liedo et al (2007) and Díaz-Fleischer et al (2009), who evaluated cage density under laboratory conditions and found that low densities resulted in individuals with increased mating competitiveness. In the same sense, the highest fl ight ability for A. ludens was obtained in MX screen towers, as they have a larger ventilation area.…”
Section: Discussionsupporting
confidence: 87%
“…This is reflected in the number of hosts parasitized and the level of superparasitism observed among mass-reared females under our experimental conditions. A similar phenomenon has been observed in fruit flies (Liedo and Carey 1996;Miyatake 1998;Cayol 2000;Liedo, Salgado, Oropeza, and Toledo 2007;Hernández, Toledo, Artiaga-Ló pez, and Flores 2009), where females become more fertile and precocious as a consequence of their adaptation to mass-rearing conditions. Ethograms suggested that the behavioral sequences in the choice of either parasitized larvae or non-parasitized larvae did not differ in wild and lab females.…”
Section: Discussionsupporting
confidence: 74%
“…The pupal weight of C. capitata has also been found to increase significantly through colonization (Liedo et al, 2007). The pupal weight of C. capitata has also been found to increase significantly through colonization (Liedo et al, 2007).…”
Section: Discussionmentioning
confidence: 89%